Suami Penjudi Sebagai Alasan Fasakh Nikah (Analisa Komparatif Penalaran Hukum Fikih Syāfi’iyyah dan Pasal 116 KHI) - Zubir, Muhammad (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
The purpose of this research is to see the concept of Syafi’iyyah Fiqh and Article 116 Compilation of Islamic Law (KHI) on husband's gambling as a reason for divorce (fasakh) and to see the basic thinking of both. This type of thesis research is a qualitative research with a normative approach, namely research conducted by examining library materials related to legal issues in everyday people's life such as divorce (fasakh) and others. From this study the authors found that according to Syafi’iyyah Fiqh, a husband who gambles is not justified as one of the reasons for divorce (fasakh). Because they do not meet the conditions for divorce that have been determined such as disabilities and others. Unless gambling can neglect his obligations as a husband. This is different from Article 116 of the Compilation of Islamic Law (KHI), in which a husband who gambles can be used as an excuse for divorce (fasakh) because he does not see the consequences. The rationale for Syafi’iyyah Fiqh, in determining the gambler's husband as the reason for divorce is to follow the principles contained in the Shafi'i school of thought. Meanwhile, the Compilation of Islamic Law (KHI) is based on previous government regulations. Namely, the Government Regulation of the Republic of Indonesia Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 concerning Marriage. This difference is based on the number of sources adopted by the Compilation of Islamic Law (KHI) such as across the four schools and others. In addition, it is adapted to the conditions of the Indonesian nation. The goal is to be guided by one legal concept in making case decisions.